Direct Blue 71 staining as a destaining‐free alternative loading control method for Western blotting. Issue 15 (2nd August 2013) - Zeng, Li; Guo, Jing; Xu, Hong‐Bo; Huang, Rongzhong; Shao, Weihua; Yang, Liu; Wang, Mingju; Chen, Jianjun; Xie, Peng
<x xml:space="preserve">Abstract</x> In Western blotting, a suitable loading control is indispensable for correcting errors in the total amount of loaded protein. Immunodetection of housekeeping proteins and total protein staining have traditionally been used as loading control methods. Direct Blue 71 (DB71) staining—a novel, sensitive, dye‐binding staining method compatible with immunodetection—may offer advantages over these traditional loading control methods. Three common neuroscientific samples (human plasma, human oligodendrocytes, and rat brain) were employed to assess DB71 staining as a loading control method for Western blotting. DB71, CBB, one traditional housekeeping protein, and one protein of interest were comparatively assessed for reliability and repeatability and linear dynamic range over 2.5–40 μg of protein loaded. DB71's effect on the reliability and repeatability and linear dynamic range of immunoreaction were also assessed. Across all three sample types, DB71 was either equivalent or superior to CBB and housekeeping protein‐based methods in terms of reliability and repeatability and linear dynamic range. Across all three sample types, DB71 staining did not impair the reliability and repeatability or linear dynamic range of immunoreaction. Our results demonstrate that the DB71 staining can be used as a destaining‐free alternative loading control method for Western blotting.